Development of hybrid scaffolds with natural extracellular matrix deposited within synthetic polymeric fibers. Issue 8 (19th April 2017) - Goyal, Ritu; Vega, Maria E.; Pastino, Alexandra K.; Singh, Shivani; Guvendiren, Murat; Kohn, Joachim; Murthy, N. Sanjeeva; Schwarzbauer, Jean E.
Abstract: A major challenge of tissue engineering is to generate materials that combine bioactivity with stability in a form that captures the robust nature of native tissues. Here we describe a procedure to fabricate a novel hybrid extracellular matrix (ECM)—synthetic scaffold biomaterial by cell‐mediated deposition of ECM within an electrospun fiber mat. Synthetic polymer fiber mats were fabricated using poly(desamino tyrosyl‐tyrosine carbonate) (PDTEC) co‐spun with poly(ethylene glycol) (PEG) used as a sacrificial polymer. PEG removal increased the overall mat porosity and produced a mat with a layered structure that could be peeled into separate sheets of about 50 μm in thickness. Individual layers had pore sizes and wettability that facilitated cell infiltration over the depth of the scaffold. Confocal microscopy showed the formation of a highly interpenetrated network of cells, fibronectin fibrils, and synthetic fibers mimicking a complex ECM as observed within tissues. Decellularization did not perturb the structure of the matrix or the fiber mat. The resulting hybrid ECM‐scaffold promoted cell adhesion and spreading and stimulated new ECM assembly by stem cells and tumor cells. These results identify a new technique for fabricating highly porous synthetic fibrous scaffolds and an approach to supplement them with natural biomimetic cues. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 2162–2170, 2017.